Design of Grating Type GaAs Solar Absorber and Investigation of Its Photoelectric Characteristics - Huang, Meihong; Wei, Kaihua; Wu, Pinghui; Xu, Danyang; Xu, Yan (Frontiers in Materials, 2021)
In recent years, as a renewable clean energy with many excellent characteristics, solar energy has been widely concerned. In this paper, we propose an ultra-broadband solar absorber based on metal tungsten and semiconductor GaAs structure. A multilayer metal semiconductor composite structure composed of W-Ti-GaAs three-layer films and GaAs gratings is proposed. The finite difference time domain method is used to simulate the performance of the proposed model. High efficiency surface plasmon resonance is excited by adjusting the geometric parameters, and the broadband absorption of up to 2,350 nm in 500–2850 nm is realized. The spectrum of the structure can be changed by adjusting the geometric parameters to meet different needs. The proposed absorber has good oblique incidence characteristics (0–60°) and high short-circuit current characteristics. The geometry of the absorber is clear, easy to manufacture, and has good photoelectric performance. It can realize solar energy collection, light heat conversion, high sensitive sensing and other functions.